WEB3: PEMBAYARAN NON-TUNAI DI ONLINE SHOP - Mgs Ilham Zuhdi; Tata Sutabri (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This research was conducted to understand the use of Web3 in non-cash payments on an online store through a case study method. Data was collected through observation and analysis of blockchain transactions. The analysis results showed that the use of Web3 in non-cash payments on online stores has advantages and disadvantages. The implications of these findings indicate that the use of Web3 can accelerate the payment process and improve transaction security. However, there are also several challenges that need to be overcome, such as technology complexity and lack of user awareness. Therefore, this research recommends continuing to develop Web3 technology and increasing user literacy about the use of Web3 in non-cash payments on online stores